Business Plan: Feed processing by youth groups in Doyogena, Ethiopia - Rudiger, Udo; Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2022)
A business plan for animal feed processing by sheep fattening youth groups in Doyogena, Ethiopia